THE PRINCIPLE OF DETERMINACY OF LEGAL RULES AS AN ELEMENT OF THE PRINCIPLE OF COMPETENT LEGISLATION - MYŚLIŃSKA, Marzena (Comparative Legilinguistics, 2017)
The Constitutional Tribunal and legal science derived the principle of competent legislation from among numerous principles stemming from the concept of a democratic legal state (article 2 of the Constitution of 1997). This principle consists of a range of detailed elements, the normative content of which constitutes the principle of the citizen’s confidence in the state and the law established by it, legal certainty and legality. The major components of this principle are as follows: the principle lex retro non agit, the principle vacatio legis, the principle of the protection of acquired rights, the principle of determinacy of legal rules. Additionally, the following principles have been distinguished: the principle pacta sunt servanta, the prohibition of changes in the tax law during a tax year, the requirement to protect the interests in progress as well as the requirement to specify the guidelines concerning the content of a regulation. The subject of this article consists of the analysis of the principle, which directly relates to the linguistic aspect of law - the principle of determinacy of legal rules. To be an effective means of communication between a legislator and those subject to established norms, legal language must be subject to certain requirements, which stem from the described principle. The essence of the principle of determinacy of legislation consists in the obligation to create laws with correct, precise and clear content. Due to the limited space of this study, I will confine myself to the problem of substantiating the binding force of the discussed principle, its content, exemplification of its violation by a legislator, factors affecting the level of determinacy in a particular case as well as the scope of unconstitutionality of legal rules that do not comply with the established requirements.